Biological Properties of Some Sepsis-Associated Low Molecular Aromatic Microbial Metabolites - N. V. Beloborodova; A. A. Osipov; A. Yu. Bedova (Антибиотики и Химиотерапия)
Physico-chemical and biological properties of sepsis-associated low molecular aromatic compounds are summarized and analysed in the review. Phenylcarbonic acids (PCAs), such as para-hydroxyphenyllactic acid (p-HPLA), phenyllactic acid (PLA), para-hydroxyphenylacetic (p-HPAA), phenylacetic acid (PAA), benzoic acid (BA), and phenylpropionic acid (PPA) are shown to have biorequlatory activity and be able to affect both bacteria and eukaryotic cells. In the review there are presented data on the diagnostic and pathogenetic value of PCAs, their bacteriostatic and bacteriocidal properties and biosynthesis by clinically significant bacterial species, as well as description of the mechanisms of microbial resistance to PCAs, the pathways of PCAs metabolism by prokaryotes, PCAs membrane transport and excretion pathways in humans, the data on the use of PCAs in clinical practice. The authors are of the opinion that PCAs of microbial origin share the metabolic and signal pathways in integration of the microbiome and man. On the basis of the literature data and personal studies the authors validated the hypothesis of possible development of new therapeutic strategies, grounded on regulation of the local and systemic balance of aromatic microbial metabolites in the human body.